De-internationalization and Re-internationalization of the Firm Business Model Innovation for Growth and Survival - Sort, Jesper Chrautwald; Taran, Yariv; Turcan, Romeo V. (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2025)
XXIII, 130 p. 11 illus.